Efeito protetor da boldina no dano neuronal, déficit de memória e resposta inflamatória em camundongos submetidos à isquemia cerebral focal permanente - Lima, Neila Maria Rocha de (2015)
Stroke is the second largest cause of death and the leading cause of disability worldwide. The ischemic process causes oxygen and glucose depletion and leads to a cascade of events including inflammation, apoptosis and oxidative stress. Substances having anti-inflammatory and antioxidant properties are being considered a new therapeutic approach for the pharmacological treatment of cerebrovascular diseases, in particular the stroke. Boldine is an alkaloid of the aporphine group found in the leaves and bark of Peumus boldus, with anti-inflammatory and anti-oxidants properties. The objective of this study was to investigate the neuroprotective effect of boldine in neuroinflammation and memory deficits induced by permanent middle cerebral artery occlusion (pMCAO) in mice. Thirty minutes before and for 5 days after pMCAO, animals received vehicle (0,025M HCl solution) or boldine (8, 16 and 25 mg / kg, ip). The quantification of cerebral infarction area, neurological scores and myeloperoxidase activity (MPO) were assessed 24 hours after pMCAO. Locomotor activity, working memory and aversive memory were assessed 72 hours after pMCAO. Episodic memory was assessed 96 hours after pMCAO and spatial memory was assessed 120 hours after pMCAO. Cresyl violet and Fluoro Jade C staining was performed 120h after pMCAO to display neuronal viability was carried out. Immunohistochemistry were made for GFAP (glial fibrillary Acid Protein), TNF-α and iNOS as inflammatory markers. Treatment with boldine (25mg / kg) significantly reduced infarct size and improved scores on neurological evaluation 24 hours after the ischemic insult. O TTC showed that the mean percentage of infarct volume was 8% in mice treated with vehicle hemispheres undergoing pMCAO. When mice were treated with boldine (25mg / kg), a significant decrease in the infarct volume to 3%. It was found also observed this treatment with boldine attenuated cell death in the cortex and striatum of mice 120 hours after the pMCAO evaluated by staining Cresil violet and Fluoro-Jade C. Ischemic injury did not alter the horizontal exploratory activity of the animals, but decreased the vertical exploration activity. Boldine at a dose of 25 mg / kg decreased this motor deficits in ischemic animals. Boldine also decreased deficits of aversive memory, spatial, episodic and working. Furthermore, pMCAO promoted increases in myeloperoxidase activity (MPO), treatment with boldine was able to reduce the increase MPO activity in the cortex. Furthermore, immunohistochemical analysis showed that TNF-α expression and iNOS, that are related to inflammation, increased after the ischemic insult and boldine reduces the increase of the expression. The pMCAO showed an increase in the immunoreactivity of GFAP, and treatment with boldine reduced this increase of activity. These results suggest that the neuroprotective effect of boldine may be related, at least in part, to its anti-inflammatory properties, however, other mechanisms, such as its antioxidant property cannot be ruled out.